Mobile platforms and multi-mobile platform development - Charaf, Hassan; Ekler, Péter; Mészáros, Tamás; Kelényi, Imre; Kővári, Bence; Albert, István; Forstner, Bertalan; Lengyel, László (Acta Cybernetica, 2014)
Mobile devices and mobile applications have a significant effect on the present and on the future of the software industry. The diversity of mobile platforms necessitates the development of the same mobile application for all major mobile platforms, which requires considerable development effort. Mobile application developers are multiplatform developers, but they prioritize the platforms, therefore, not all platforms are equally important for them. Appropriate methods, processes and tools are required to support the development in order to achieve better productivity. The main motivation of our research activity is to provide a method, which increases the development productivity and the quality of the applications and also reduces the time to market. The paper discusses our model-driven results on the field of multi-mobile platform development.